P145 Introduction and trial of a "chemsex" support service in a south west london gu clinic. (18th May 2015) - Nathan, Bavithra; Waters, Julia; Simms, Richard; Green, Simon; Husbands, Clare; Milgrew, Graham; McCarthy, Gill
Abstract : Background/introduction: Since 2013 our centre has recognised a problem of recreational use drug associated with sex amongst MSM. Aim(s)/objectives: A joint survey with the local commissioners was set up to establish the extent of the problem in the borough and to identify a need for further services. Methods: 100 HIV negative MSM and 50 HIV positive MSM completed a patient survey with questions regarding recreational drug use related to "chemsex". Results: Results indicated a high level of drug use with 60% (90/150) reporting any drug use and 21% (32/150) specifically using party drugs in the last 6 months. Clients were asked where they would like to have a specialist drug service and the majority preferred the sexual health clinic as an acceptable venue 37% (56/150). A weekly "in-reach" service was set up with the local Drug Service to run alongside the MSM evening clinic. From August to December 2014, there were 15 clinics in total with 21 visits (max capacity 30 visits). 25% of those seen were from the local borough; the rest of the clients were from neighbouring boroughs. Discussion/conclusion: The service to date has been a clinical and operational success. A patient satisfaction questionnaire completed by 13 clients noted 92% were happy to be seen at this venue, 85% felt the provision of this service was worthwhile and 85% would recommend this service to others. Further work in this area with a targeted MSM history proforma, chemsex leaflet and needle exchange schemes are also being developed.